Analisis Pengaruh CAR, NDF, FDR, ROA, ROE dan BOPO Terhadap Pembiayaan Pada BPRS Periode 2019-2023 - Zamzamah, Hanabilla; Woyanti, Nenik (JEMAP, 2025)
As intermediary institutions, Sharia Rural Banks (BPRS) collect funds from the public and channel them into financing. In practice, the amount of financing provided by these banks is influenced by many factors, which do not always align with existing theories. Therefore, this study aims to examine the effect of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Assets (ROA), Return on Equity (ROE), and Operational Expenses to Operational Income (BOPO) on financing in BPRS. The data used for this study is secondary monthly time series data published by the Financial Services Authority of Indonesia (OJK) in the Islamic Banking Statistics with 5 years observation period that is January 2019- December 2023. The method used in this study is quantitative analysis with multiple linear regression method processed using SPSS version 25. The results of this study indicate that the CAR and FDR variables has significant positive effect on financing in BPRS. The NPF and BOPO variables has significant negative effect on financing in BPRS. And the other variables, ROA and ROE, has no significant negative effect on financing in BPRS